DNA Methylation as a Marker of Body Shape in Premenopausal Women - Divoux, Adeline; Eroshkin, Alexey; Erdos, Edina; Sandor, Katalin; Osborne, Timothy F.; Smith, Steven R. (Frontiers in Genetics, 2021)
Preferential accumulation of fat in the gluteo-femoral (GF) depot (pear shape) rather than in the abdominal (A) depot (apple shape), protects against the development of metabolic diseases but the underlying molecular mechanism is still unknown. Recent data, including our work, suggest that differential epigenetic marking is associated with regulation of genes attributed to distinct fat distribution. Here, we aimed to compare the genomic DNA methylation signatures between apple and pear-shaped premenopausal women. To investigate the contribution of upper and lower body fat, we used paired samples of A-FAT and GF-FAT, analyzed on the BeadChip Methylation Array and quantified the differentially methylated sites between the 2 groups of women. We found unique DNA methylation patterns within both fat depots that are significantly different depending on the body fat distributionAround 60% of the body shape specific DNA methylation sites identified in adipose tissue are maintained ex-vivo in cultured preadipocytes. As it has been reported before in other cell types, we found only a hand full of genes showing coordinated differential methylation and expression levels. Finally, we determined that more than 50% of the body shape specific DNA methylation sites could also be detected in whole blood derived DNA. These data reveal a strong DNA methylation program associated with adipose tissue distribution with the possibility that a simple blood test could be used as a predictive diagnostic indicator of young women who are at increased risk for progressing to the apple body shape with a higher risk of developing obesity related complications.